A Comparison of Femoral Lengthening Methods Favors the Magnetic Internal Lengthening Nail When Compared with Lengthening Over a Nail. Issue 2 (July 2018) - Fragomen, Austin T.; Kurtz, Anton M.; Barclay, Jonathan R.; Nguyen, Joseph; Rozbruch, S. Robert
Background: Bone lengthening with an internal lengthening nail (ILN) avoids the need for external fixation and requires one less surgical procedure than lengthening over a nail (LON). However, LON has been shown to be superior to femoral internal lengthening using a mechanical nail. The magnetic ILN, a remote-controlled and magnet-driven device, may have overcome the weaknesses of earlier internal lengthening technology and may be superior to LON. Questions/Purposes: (1) Is the magnetic ILN more accurate than LON for femoral lengthening? (2) Does the magnetic ILN demonstrate more precise distraction rate control than LON? (3) Does the magnetic ILN result in faster regenerate site healing, with more robust callus, than LON? (4) Does the magnetic ILN result in fewer complications, including impediments to knee motion, than LON? Methods: We conducted a retrospective comparison of the records and radiographs of 21 consecutive patients with 22 femoral lengthenings using LONs and 35 consecutive patients with 40 femoral lengthenings using remote-controlled magnetic ILNs. Primary outcomes measured included accuracy, distraction rate precision, time to bony union, final knee range of motion, regenerate quality, and complications. The minimum follow-up times for the LON and ILN cohorts were 13 and 21 months, respectively. Results: Patients treated with ILN had a lower post-treatment residual limb-length discrepancy (0.3 mm) than those treated with LON (3.6 mm). The rate of distraction was closer to the goal of 1 mm/day and more tightly controlled for the ILN cohort (1 mm/day) than that for the LON group (0.8 mm/day; SD, 0.2). Regenerate quality was not significantly different between the cohorts. Bone healing index for ILN was not statistically significant. Time to union was shorter in the ILN group (3.3 months) than that in the LON group (4.5 months). A lower percentage of patients experienced a complication in the ILN group (18%) than in the LON group (45%). Knee flexion at the end of distraction was greater for ILN patients (105°) than that for LON patients (88.8°), but this difference was no longer observed after 1 year. Conclusions: Femoral lengthening with magnetic ILN was more accurate than with LON. The magnetic ILN comports the additional advantage of greater precision with distraction rate control and fewer complications. Both techniques afford reliable healing and do not significantly affect knee motion at the final follow-up. The magnetic ILN method showed no superiority in regenerate quality and healing rate.